Analysis of a speed for athletes of handball Fraiburgo-SC - Gutierrez, Felipe de Almeida (2012)
Agility is an important foundation for Handball therefore requires much movement on the court sport. Improving agility that causes the athlete tested positive for the sport. Through a training program that involves the development of agility andspeed favors the performance of athletes in this sport performance. With the objective to identify the effect of an Agility Program to be implemented in young, became per experiment, male athletes aged between 14 and 17 years, working in the sport of Handball in Fraiburgo, Santa Catarina. The Shuttle Run protocol was used in order to provide a specific physical agility training, which involved the speed of the athlete to make it possible to compare data before and after testing them. For the analysis of research adopted the method "t" Student, and also the program average and standard deviation. After the completion of pre-tests were performed several specific activities according to technical references as part of a training occurred three times a week forthree months. At the same time, athletes performed other types of exercises like lateral displacement, zig-zag cones with or without the ball, shooting speed of 15/20 meters. Then we applied the post-test measure that allowed the improvement in speed by the subjects. With this quantitative experimental research has achieved its goal with the athletes since the proceeds from a training program showed a significant improvement in agility of these athletes.